Effect of Cultivar and Gelling Agent on In Vitro Multiplication of Gerbera (Gerbera jamesonii Bolus) Shoots (University of Khartoum Journal of Agricultural Sciences, 2023)
An experiment was conducted to study the effect of cultivar andconcentration of agar and gelrite on in vitro multiplication of gerbera(G.jamesonii) shoots. Sterile in vitro growing shoots of the gerbera cultivarsAmeretto, Red Bull, Ruby Red, Yellowish green and Crillo were placed inglass jars containing nutrient media with different concentrations of agar andgelrite. There was a significant interaction between the gelling agents’concentrations and the gerbera cultivars. There was a decrease in themultiplication and vitrification rates with the increase of the concentration ofthe different gelling agents in the nutrient medium.
Keywords: Gerbera jamesonii; gelling agent; shoot multiplication